Periode Kritis Jagung (Zea mays L.) Berkompetisi dengan Gulma di Lahan Kering - Ngawit, I Ketut; Santoso, Bambang Budi; Azhari , Anjar Pranggawan (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
Research into the critical phase of weed competition in maize aims to determine weed control at the right time. The study used a randomized block design consisting of eight treatments with weed-free (WWF) and weed-free (WF) plant age periods up to 10, 20, 30, 40, 50, 60, 70, and 80 days after planting (DAP). Each treatment was randomly repeated in three blocks, resulting in 54 experimental units The observation parameters include weed population, dry biomass weight of weeds and maize, plant height, leaf area, ear length, ear diameter and dry weight of maize kernels per plot. Data analysis using analysis of variance and William's statistical test. The results of the study showed that the critical period for corn competition with weeds on dryland was about 20 - 30 DAP when the corn was planted. If weeds are removed after the plants are more than 30 days old, the harvest cannot be saved. Plants competing with weeds for 40, 50, 60, 70, and 80 days experienced yield reductions of 60.32%, 82.84%, 98.66%, 99.99%, and 99.99%, respectively. In contrast, plants that were only weed-free up to the age of 10, 20, and 30 days showed yield losses of 98.66%, 80.16%, and 61.40%, respectively. It is recommended to start controlling corn weeds on dry land 20 days after planting and to avoid weeding 30 days after planting.